Nucleosome assembly protein 1-like 5 alleviates Alzheimer’s disease-like pathological characteristics in a cell model - Wang, Bingyan; Liu, Weiying; Sun, Fengxian (Frontiers in Molecular Neuroscience, 2022)
Alzheimer’s disease (AD) remains one of the most common dementias of neurodegenerative disease-related diseases. Nucleosome assembly protein 1-like 5 (NAP1L5) belongs to the NAP1L protein family, which acts as a histone chaperone. However, the function and mechanism of NAP1L5 in AD are still unclear. Bioinformatics analysis, RT-qPCR, and western blotting results showed that NAP1L5 was downregulated in the brain tissues of AD patients and a mouse cell model of AD. NAP1L5 overexpression alleviated (Amyloid-β precursor protein) APP metabolism, neuroinflammation, and Tau phosphorylation. Furthermore, we demonstrated that NAP1L5 regulated the AD-like pathological characteristics through the GSK3B/Wnt/β-Catenin signaling pathway. In sum, these results suggested that NAP1L5 overexpression has neuroprotective effects and might act as potential biomarker and target for the diagnosis and treatment of AD.